A Post-Pandemic Assessment of the Sustainable Development Goals - Benedek, Dora.; Gemayel, Edward; Senhadji, Abdelhak; Tieman, Alexander (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic hit countries' development agendas hard. The ensuing recession has pushed millions into extreme poverty and has shrunk government resources available for spending on achieving the United Nations Sustainable Development Goals (SDGs). This Staff Discussion Note assesses the current state of play on funding SDGs in five key development areas: education, health, roads, electricity, and water and sanitation, using a newly developed dynamic macroeconomic framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; Policy Option; Sustainable Development Goals and Development; Underground Econom